2020
DOI: 10.1021/acs.jpclett.0c01078
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Electron Transfer in a Carbon Dot–Polyoxometalate Nanohybrid

Abstract: Using solar radiation to fuel catalytic processes is often regarded as the solution to our energy needs. However, developing effective photocatalysts that are active under visible light has proven to be difficult, often due to the toxicity, instability, and high cost of suitable catalysts. We engineered a novel photoactive nanomaterial obtained by the spontaneous electrostatic coupling of carbon nanodots with [P2W18O62]6–, a molecular catalyst belonging to the class of polyoxometalates. While the former are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Today, nanotechnologies could provide new answers to these old problems. In particular, coupling nanomaterials with different electronic characteristics into a single device provides fundamentally new routes in materials science to develop efficient nano-photoelectrodevices for artificial photosynthesis, photocatalysis, and photovoltaics. Crucial requirements for these applications are the use of low cost materials and the possibility of sensitively controlling their characteristics to allow the fine tuning of the devices . Carbon-based nanomaterials are an area of huge interest in nanoscience motivated by their unsurpassed chemical versatility and diverse electronic properties which can be finely tailored for applications.…”
Section: Introductionmentioning
confidence: 99%
“…Today, nanotechnologies could provide new answers to these old problems. In particular, coupling nanomaterials with different electronic characteristics into a single device provides fundamentally new routes in materials science to develop efficient nano-photoelectrodevices for artificial photosynthesis, photocatalysis, and photovoltaics. Crucial requirements for these applications are the use of low cost materials and the possibility of sensitively controlling their characteristics to allow the fine tuning of the devices . Carbon-based nanomaterials are an area of huge interest in nanoscience motivated by their unsurpassed chemical versatility and diverse electronic properties which can be finely tailored for applications.…”
Section: Introductionmentioning
confidence: 99%
“…8 In this regard, CNDs have been decorated with photo-and redox-active building blocks for energy and/or charge transfer processes, artificial photosynthesis, and, more recently, solar energy conversion devices. 9,10 Leading examples are the combination with SWCNTs, 11 polyoxometalates, 12 or transition metal dichalcogenides. 13 CNDs have been covalently grafted with electron-donating π-extended tetrathiafulvalenes, 14 phthalocyanines, 15 and porphyrins.…”
mentioning
confidence: 99%
“…An important feature of CNDs is their duality in charge transfer events acting either as electron donor or as electron acceptor . In this regard, CNDs have been decorated with photo- and redox-active building blocks for energy and/or charge transfer processes, artificial photosynthesis, and, more recently, solar energy conversion devices. , Leading examples are the combination with SWCNTs, polyoxometalates, or transition metal dichalcogenides …”
mentioning
confidence: 99%
“…[59] Finally, a recent study demonstrated the photoinduced electron transfer from CDs to [P 2 W 18 O 62 ] 6− polyoxometalate arrays, expanding the field of nanostructures being so far interfaced with these unique fluorescent carbon nanoparticles. [74] In this case, the pH-tunable surface charge of CDs enabled the development of attractive electrostatic forces with the negatively charged [P 2 W 18 O 62 ] 6− . The utilized CDs were derived by nitration of a pyrene powder, followed by an alkaline hydrothermal treatment.…”
Section: Supramolecular Functionalization Of As-derived Cdsmentioning
confidence: 99%